Nanoscaled pearl powder accelerates wound repair and regeneration in vitro and in vivo. (3rd June 2019) - Chen, Xi; Peng, Li-Hua; Chee, Seng-Sing; Shan, Ying-Hui; Liang, Wen-Quan; Gao, Jian-Qing
Abstract: Pearl powder has been used to treat many diseases like palpitations, insomnia, and epilepsy for thousands of years in Chinese medicine. It has demonstrated antioxidant, antiaging, antiradiative, and tonic activities. Pearl powder contains multiple active proteins, which are nutritious for skin cells and might be advantageous for wound repair and regeneration. However, its healing effect in vivo was not reported yet. This study aims to investigate the effects and the underlying mechanism of the pearl powders with different particle sizes in wound treatment. Briefly, the pearl powder with different sizes was characterized for their particle sizes and morphology. The protein release profiles of these powders were also studied. The influence of the different size of pearl powder in the proliferation, migration of skin cells was evaluated. Then, with the rat skin excision model, the effect of pearl powder on wound repair and regeneration was investigated. It was demonstrated that, all the micro and nanosized pearl powders could both increase the proliferation and migration of skin cells and accelerate the wound closure, as well as significantly enhanced the biomechanic strength of the healed skins. Moreover, the pearl powder treatment could improve the formation and regular deposition of collagen, and enhance the skin angiogenesis. Among all these in vitro and in vivo investigations, nanoscale pearl powder expressed the highest efficiency for healing. The mechanism might be contributed to the increased release of active proteins, enhanced tissue attachment, and the increased cellular uptake for the nano powder at the topical site.